Enhance Successful Identification of E-Government Management in Realizing Good Government Governance in the Government of the City Of Binjai - Nst, Anggi Pratama; Sebayang, Saimara; Darma Nst, Dito Aditia (Budapest International Research and Critics University, 2021)
This study aims to determine whether the variable identification of the success of E-Government affects Good Government Governance. This study uses the SEM-Partial Least Square (PLS) approach. PLS is a component-based or variant-based Structural Equation Modeling (SEM) equation model. Hypothesis testing is carried out using the Bootstrap resampling method with a minimum number of bootstrap as many as 117 and the number of cases must be the same as the number of observations in the original sample. The results of this study prove that the identification of the success of E-Government affects Good Government Governance. The conclusion is that ten factors are accepted as critical success factors of E-Government namely Vision, Mission and Goals, strategy, security, collaboration, infrastructure, leadership support, organizational culture, finance,Community Participation, Upholding the Rule of Law, Caring for the Community, Transparency, Responsibility, fair, Effectiveness and Efficiency and Accountability.